Simulation-Based Learning Innovation To Create Effective Learning In Fiqh Subjects - Alfauzan Amin; Novriyana, Yola (Medina-te : Jurnal Studi Islam, 2024)
Simulation-based learning helps students improve their interaction and communication skills in groups. The simulation method also gives them the opportunity to behave, which is considered in accordance with the learning objectives. the purpose of writing this journal article is to understand the importance of simulation learning to create effective learning in fiqh subjects. The research method used in this study is a library method with books, journals, articles and web pages about simulation-based learning, learning effectiveness and fiqh learning as the main sources of information. The results of this study are simulations in fiqh learning have many good impacts, including students being able to understand and practice the material learned into everyday life and educators can identify which students already understand and students who still need guidance, there are 3 types of simulation-based learning including 1) role playing, 2) socio drama and 3) playing simulations.